Towards a guided atom interferometer based on a superconducting atom chip - Müller, T. (2014)
We evaluate the realization of a novel geometry of a guided atom interferometer based on a high-temperature superconducting microstructure. The interferometer-type structure is obtained with a guiding potential realized by two current carrying superconducting wires in combination with a closed superconducting loop sustaining a persistent current. We present the layout and realization of our superconducting atom chip. By employing simulations, we discuss the critical parameters of the interferometer guide in particular near the splitting regions of the matter waves. Based on measurements of the relevant chip properties, we discuss the application of a compact and reliable on-chip atom interferometer.